The role of PKC/PKR in aging, Alzheimer's disease, and perioperative neurocognitive disorders - Lu, Wenping; Tang, Sailan; Li, Ao; Huang, Qiuyue; Dou, Mengyun; Zhang, Ye; Hu, Xianwen; Chang, Raymond Chuen Chung; Wong, Gordon Tin Chun; Huang, Chunxia (Frontiers in Aging Neuroscience, 2022)
Abstract Background: The incidence of perioperative neurocognitive disorders (PND) is reportedly higher in older patients. Mitochondrial and synaptic dysfunction have consistently been demonstrated in models of aging and neurodegenerative diseases; nonetheless, their role in PND is not well understood. Methods: The Morris water maze and elevated plus maze tests were used to assess the learning and memory abilities of both C57BL/6 and 3×Tg-AD mice of different ages (8 and 18 months). PND was induced by laparotomy in C57BL/6 mice and 3×Tg-AD mice (8-month-old). Markers associated with neuroinflammation, mitochondrial function, synaptic function and autophagy were assessed postoperatively. The roles of the protein kinase C (PKC) and double-stranded RNA-dependent protein kinase (PKR) were further demonstrated by using PKC-sensitive inhibitor bisindolylmaleimide X (BIMX) or PKR-/- mice. Results: Significant cognitive impairment was accompanied by mitochondrial dysfunction and autophagy inactivation in both aged C57BL/6 and 3×Tg-AD mice. Laparotomy induced a significant neuroinflammatory response and synaptic protein loss in the hippocampus. Cognitive and neuropathological changes induced by aging or laparotomy were further exacerbated in 3×Tg-AD mice. Deficits in postoperative cognition, hippocampal mitochondria, autophagy and synapse were significantly attenuated after pharmacological inhibition of PKC or genetic deletion of PKR. Conclusions: Our findings suggest similar pathogenic features in aging, Alzheimer's Disease and PND, including altered mitochondrial homeostasis and autophagy dysregulation. Besides, laparotomy may exacerbate cognitive deficits associated with distinct neuronal inflammation, mitochondrial dysfunction, and neuronal loss independent of genetic background. The dysregulation of PKC/PKR activity may participate in the pathogenesis of these neurodegenerative diseases.